A censura ao direito de sonhar em Quarto de despejo, de Carolina Maria de Jesus - Luciana Paiva Coronel (Estudos de Literatura Brasileira Contemporânea)
This study is based on the understanding of literature as a fundamental human right. It analyses the literary dimension and the feminine imagery that are found in Beyond all pity by Carolina Maria de Jesus. Our goal is to highlight the author‟s skill to create resourceful representations of her miserable daily routine and through this oppose to the usual perception of her text as a bare documentary on Brazil‟s starvation in the 1950s. We tried to point out that there was some implicit censorship among cultural m ediators to prevent a subaltern woman from being seen as a writer, so that she would only find a place in the mere protest scene. Therefore, we understand that Carolina‟s work found echo of many authorized voices and thus enriches Brazilian contemporary li terary scene with greater representativeness.